2018
DOI: 10.14419/ijet.v7i2.29.14291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Graduate Students Employability from Employer Perspective: Review of the Literature

Abstract: Graduate employability is a critical issue in Higher Education. Employers are expecting not only the subject knowledge from the students to compete with the current industry demands, but also additional skills to face corporate battles and challenges. The aim of this research is to identify the skills demanded by the employers and to incorporate them in the learning outcomes of higher education. This research aims to review and analyses all the papers published from 2010 until now regarding the evaluation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Presently, higher education institutions shoulder a substantial degree of responsibility. Eldeen et al (2018) have previously emphasised the importance of higher education institutions in cultivating the employability skills of their graduates. Therefore, universities must consider stakeholders' perspectives to provide their graduates with the expertise and understanding needed to fulfil the industry's demands.…”
Section: Employability Skills As Career Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, higher education institutions shoulder a substantial degree of responsibility. Eldeen et al (2018) have previously emphasised the importance of higher education institutions in cultivating the employability skills of their graduates. Therefore, universities must consider stakeholders' perspectives to provide their graduates with the expertise and understanding needed to fulfil the industry's demands.…”
Section: Employability Skills As Career Driversmentioning
confidence: 99%
“…Presently, higher education institutions shoulder a substantial degree of responsibility. Eldeen et al . (2018) have previously emphasised the importance of higher education institutions in cultivating the employability skills of their graduates.…”
Section: Introductionmentioning
confidence: 99%
“…The shifting skills/competencies sought by modern employers have led to a corresponding need to transform education and teaching practices to adequately prepare the emerging workforce for twenty-first century job requirements (Binkley et al, 2012;Holtzman & Kraft, 2011;Mulryan-Kyne, 2021). However, it has been observed that university teaching not only promotes solitary learning experiences that impede the attainment of profound understanding (Lea et al, 2003;Baeten et al, 2010), but they are also often dominated by abstract concepts, and content that lack meaningful connections to students' everyday experiences (Lombardi & Oblinger, 2007;Willison, 2018) ultimately failing to help students to either develop deep conceptual understanding (Mulryan-Kyne, 2010;Schank , 2019;Schroeder et al, 2007;Eldeen et al, 2018) or evolve into critical thinkers capable of profound reflection for personal growth and societal change (Espinoza & Vossoughi, 2014;Schank, 2019).…”
Section: Introduction and Study Backgroundmentioning
confidence: 99%
“…This assertion was corroborated in a study of employers' expectation of employability skills of Estate Management graduates in Nigeria (Ayedun et al, 2013) which revealed that employers expect certain basic skills from job seekers. Eldeen et al (2018) established that employers in various countries including USA, Ireland, South Africa, Australia among others, expect graduates to possess skills other than mere subject knowledge skills. Saad and Majid (2014) blamed the educational system and practices in developing countries which focus on theoretical concepts rather than practical learning on the unemployment challenges, thereby reducing graduates' chances of meeting the demands of their employers.…”
Section: 10 Introductionmentioning
confidence: 99%